The relationship between subduction zone redox budget and arc magma fertility - Evans, Katy; Tomkins, A. (Elsevier Science BV, 2011)
A number of lines of evidence point to a causal link between oxidised slab-derived fluids, oxidised sub-arc mantle, and the formation of economic concentrations of metals such as Cu and Au that require oxidised magmas. However, trace element evidence from some trace element and isotope data suggests that sub-arc mantle is no more oxidised than mantle elsewhere. A simple analytical model is applied to constrain the evolution of sub-arc mantle oxidation state as a function of redox-budget fluxes from the subducting slab. Influential variables include the solubility of Fe3+ and SO42− in slab-derived fluids, the geometry of the infiltration of slab-derived fluids in sub-arc mantle, the coupling between slab-derived and arc-output redox budgets, and the concentration of redox-buffering elements such as Fe and S in the sub-arc mantle. Plausible Archean and Proterozoic redox budget fluxes would not have created oxidised sub-arc mantle without input from ferric iron or sulphate dissolved in non-aqueous fluids such as silicate melts. Aqueous-borne Phanerozoic redox budget fluxes, on the other hand, which are dominated by the sulphate component, could have increased sub-arc fo2 by up to three log10 units. The results are generally consistent with the proposed elevated fo2 for sub-arc mantle, but no resolution was found for the apparent contradiction between high proposed fO2 values derived from iron-based oxybarometry and the lower values inferred from trace element and isotope evidence Increases in sub-arc mantle fO2 are favoured by focussed fluid infiltration and magma generation, weak coupling between slab and arc-output redox budgets, and restricted redox-buffering in the sub-arc mantle.Fertile arc segments for ore deposits associated with oxidised magmas require fluid chemistry and pressure–temperature gradients that enhance Fe3+ and SO42 − solubility in aqueous and silica-rich fluids, tectonic stress regimes that favour focussed transfer of components into the sub-arc mantle, and a relatively weak redox buffer for the sub-arc mantle. The paucity of Cu and Au deposits associated with oxidised magmas in Precambrian rocks may be explained as a consequence of a lack of subducted oxidised material, rather than simply as a consequence of preservation potential. Additionally, the reduced nature of subducted material in the Precambrian may have caused S and metal enrichment in the sub-arc mantle.